2019
DOI: 10.5552/crojfe.2019.532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Best Management Practices for Erosion Control on Machine Operating Trails

Abstract: Ground-based mechanized forest operations often lead to increased runoff and soil loss on unbound forest roads and machine operating trails, which in turn can impede the technical trafficability of machines and cause negative impacts on the environment. The aim of this study was to evaluate the effectiveness of three Best Management Practice (BMP) treatments used to control erosion occurring on machine operating trails. The treatments included water bar, water bar and hardwood brush (H-brush), and water bar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
2
7
0
2
Order By: Relevance
“…Osim taloženja, rizici povezani s kretanjem sedimenta, mogu uzrokovati degradaciju kvalitete vode transportom sedimenta u potoke (Grace, 2006). Šumski kamionski putevi i traktorski putevi/vlake mogu uzrokovati značajno povećanje površinskog oticanja i prinos sedimenta, posebno kad su tla ogoljena i uz visoku frekvenciju kretanja mehanizacije (Solgi et al, 2019), pri čemu se negativan efekat smanjuje uz izgradnju objekata za preusmjeravanje površinskih voda (Solgi et al, 2021). Ukoliko se traktorski putevi/vlake ne saniraju nakon završenih radova na eksploataciji šuma skoro je izvjesno intenziviranje erozionih procesa (Bajrić, 2012).…”
Section: Dynamics Of Development Of Erosion Processes On Skid Roads -...unclassified
See 1 more Smart Citation
“…Osim taloženja, rizici povezani s kretanjem sedimenta, mogu uzrokovati degradaciju kvalitete vode transportom sedimenta u potoke (Grace, 2006). Šumski kamionski putevi i traktorski putevi/vlake mogu uzrokovati značajno povećanje površinskog oticanja i prinos sedimenta, posebno kad su tla ogoljena i uz visoku frekvenciju kretanja mehanizacije (Solgi et al, 2019), pri čemu se negativan efekat smanjuje uz izgradnju objekata za preusmjeravanje površinskih voda (Solgi et al, 2021). Ukoliko se traktorski putevi/vlake ne saniraju nakon završenih radova na eksploataciji šuma skoro je izvjesno intenziviranje erozionih procesa (Bajrić, 2012).…”
Section: Dynamics Of Development Of Erosion Processes On Skid Roads -...unclassified
“…O značaju proučavanja erozionih procesa na traktorskim putevima/vlakama jasno ukazuju brojne studije i naučno-istraživački radovi koji su provedeni od strane više istraživača (Meghatan and Kidd, 1972;Jeličić 1983Jeličić , 1990Rebula 1991;Krpan i drugi, 1993;Tomašić, 1994;Pičman i Pentek 2001, Sasaki 2004, Eliasson 2005Bajrić 2012Bajrić , 2015Bajrić , 2021Grace 2006;Grushecky et et al, 2007;Elliot et al, 2009;Naghdi et al, 2012;Bagheri et al, 2012;Turk & Yildiz, 2019;Solgi et al, 2019;DeArmond et al, 2021;Jourgholami et al, 2021 i drugi istraživači).…”
Section: Dynamics Of Development Of Erosion Processes On Skid Roads -...unclassified
“…Most of the damage that occurs in mechanized timber harvesting is observed in the soil in the immediate vicinity and directly on the skidding or operational trails (Matthies et al 1995, Haas et al 2015. Mixing of the top soil layer, its compaction and displacement in combination with rut compaction can have a negative environmental impact (Cambi et al 2015, Haas et al 2015, Solgi et al 2019. Many authors indicate that soil degradation, as a result of machine harvesting, can significantly affect both the quality of growing trees and the deterioration of forest health (Ulrich et al 2003, Murphy 2004, Ampoorter et al 2007, Malík and Dvořák 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Agherkakli et al (2014) revealed a high protective role of slash, particularly on steep skid trails. Creation of water diver-https://doi.org/10.17221/61/2020-JFS sion structures to reduce runoff generation and sediment yield such as water bars can be a very effective method for limiting sediment delivery to adjacent areas (Solgi et al 2019). Solgi et al (2019) used the treatments of water bar, water bar and hardwood brush, and water bar and softwood brush to control runoff and soil loss from skid trails.…”
mentioning
confidence: 99%
“…Creation of water diver-https://doi.org/10.17221/61/2020-JFS sion structures to reduce runoff generation and sediment yield such as water bars can be a very effective method for limiting sediment delivery to adjacent areas (Solgi et al 2019). Solgi et al (2019) used the treatments of water bar, water bar and hardwood brush, and water bar and softwood brush to control runoff and soil loss from skid trails. Results of this study showed that the amount of runoff and soil loss decreased consistently as the thickness of the brush mat increased.…”
mentioning
confidence: 99%